ANALISIS EKSISTENSI PASAR TRADISONAL DI KOTA BANDA ACEH - Heri Setiadi; Nur Aidar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractThis study aims to determine the factors that influence the existence of traditional market in Banda Aceh City. The variables in this study include market characteristics, traders characteristics, buyer characteristics and perceptions of market existence. In this study, the authors used a sample of 60 traders, 60 buyers and 3 managers spread over three traditional market, namely Kartini , Peuniti and Setui market. Based on the results of the research on trader's perceptions of the existence of traditional market in Banda Aceh City, the things that attract bayers to the market are safety, comfort, and the quality of goods that are still good and fresh. The results of the research of buyers to traditional market, the existence of traditional market close to settlements and the location of residence is also an important thing for visitors to keep shopping at the market. In order to maintain the existence of traditional market, market managers are trying to improve the security, convenience of traders and traditional market bayers and improve the existing facilities in traditional market.Keywords: Existence, Charateristic, Traditional markets, Traders, Buyers